People Risk Management : A Practical Approach to Managing the Human Factors That Could Harm Your Business /: A Practical Approach to Managing the Human Factors That Could Harm Your Business. (2015) - Blacker, Keith; McConnell, Patrick (Patrick J.)
No abstract available